Incidence, risk factors and clinical outcomes of septic acute renal injury in cancer patients with sepsis admitted to the ICU: A retrospective study - Yang, Yong; Dong, Jun; Chen, Xiaojie; Chen, Renxiong; Wang, Hongzhi (Frontiers in Medicine, 2022)
Background: The purpose of this study was to clarify the incidence, risk factors and clinical outcomes of septic acute kidney injury (AKI) in cancer patients with sepsis admitted to the intensive care unit (ICU). Methods: A total of 356 cancer patients admitted to the ICU due to sepsis from January 2016 to October 2021 were analyzed retrospectively. According to the incidence of septic AKI, all patients were divided into the non-AKI group (n=279) and the AKI group (n=77). The clinical data after ICU admission were compared between the above two groups, and the risk factors and the clinical outcomes of septic AKI in the ICU were identified. Results: The incidence of septic AKI in all patients was 21.6% (77/356). LASSO regression and logistic regression all showed that lactate, sequential organ failure assessment (SOFA) score and septic shock were closely related to the occurrence of septic AKI. In terms of clinical outcomes after ICU admission, the rate of mechanical ventilation (MV) and continuous renal replacement therapy (CRRT), MV time, hospitalization time and 28-day mortality in the ICU were significantly higher in the septic AKI group than in the non-septic AKI group. Among the three subgroups of septic AKI (AKI combined with septic shock, septic cardiac dysfunction or acute respiratory failure), the mortality of patients in the subgroup of AKI combined with septic shock was significantly higher than others. CRRT has no significant effect on the short-term outcome of these patients. Conclusions: Lactate level, SOFA score and septic shock were closely related to the occurrence of septic AKI in the ICU. The clinical outcomes within 28 days after ICU admission of cancer patients with septic AKI were worse than those without septic AKI. The short-term outcome was worse in patients with septic AKI complicated with septic shock. CRRT has no significant effect on the short-term prognosis of cancer patients with septic AKI in the ICU.